Factors influencing sonographer-led bowel ultrasound services in the UK. Issue 2 (March 2023) - Babington, E.A.; Hynes, C.; Lawal, O.
Abstract: Introduction: There is a growing understanding of the potency of bowel ultrasound leading to an increasing application of ultrasound in examining different bowel conditions. However, sonographers' involvement in bowel ultrasound is under-researched. This study investigated the factors influencing sonographers' experience in adult bowel ultrasound. Methods: A convenience sampling method was used to promote the study in April 2021. A mixed methods online questionnaire was utilised to explore the participants' views. Quantitative data were analysed using descriptive analysis on Excel, while qualitative data were analysed using inductive thematic analysis. Results: Almost half of the participants (53%; n = 16) indicated low confidence in using ultrasound to examine the bowel for abnormalities. While 63% of the participants reported having high confidence in examining the bowel for suspected appendicitis, 70% (n = 21) reported low confidence in carrying out ultrasound in examining Inflammatory bowel disease. Furthermore, 23 participants (77%) indicated a high interest in bowel ultrasound training. Qualitative findings revealed mixed opinions on bowel ultrasound practice. Factors influencing sonographers' experience are the need for more training opportunities, preference for other imaging modalities, management challenges, radiologists' influence, sonographers' perspectives, and positive perspectives. Conclusion: Several factors influence sonographers' confidence in using ultrasound for bowel abnormalities. However, the findings emphasise the need for more research into the future design and implementation of sonographers' bowel ultrasound training. Implication for practice: This study brings new insight to an under-researched area on the scope of sonography practice, highlighting some sonographers' experience, opinions, and involvement in bowel ultrasound. It further strengthens the argument for more training to be made available to sonographers on bowel ultrasound.